Risks of RFID. - Neumann, Peter G.; Weinstein, Lauren (Communications of the ACM, 2006)
An analysis of Radio-Frequency IDentification (RFID) is presented. Like most other technologies, RFID systems have pluses and minuses. In their most common applications, passive RFID tags enable rapid contact less determination of the tags' serial numbers, in theory helping to reduce erroneous identifications. However, this technology becomes dangerous whenever the binding between the tag and its context of use is in doubt. This situation is similar to Social Security numbers, which are themselves useful as identifiers but not as authenticators, with a wide range of proven abuses. RFID benefits may be negated by numerous opportunities for accidental or intentional misuse of the technology and its supporting systems, along with a wide range of issues relating to system and data integrity, personal well-being, and privacy.